Investment Decisions – Influence of Behavioural Factors - Shanmugsundaram, V.; Balakrishnan, V. (Indian Journal of Finance, 2011)
Investors frequently make poor decisions caused by psychological biases and emotions. Investments are made with an avowed objective of maximizing the wealth. Investors need to make rational decisions for maximizing their returns based on the information available by taking judgements free from emotions. Researchers have found that investors often make errors - like failing to react quickly enough to new information that challenges their existing options. Investor behaviour is characterized by overexcitement and over reaction in both rising and falling stock markets. Behavioural finance, a new paradigm of finance, seeks to supplement the standard theories of finance by introducing behavioural aspects to the decision making process. It acquires importance, since decisions are not guided by rationality or prudence, but by the emotions - greed and insufficient knowledge in capital market operations and in the highly overloaded information environment. This paper investigates how investors interpret and act on information to make informed investment decisions. Also this research seeks to understand and predict systematic financial market implications of psychological decision making processes. Empirical evidence suggests that demographic factors influence investors’ investment decision.